COVID-19 Pandemic and its Effect on the Business Development Center UIN Sunan Kalijaga Yogyakarta: An Islamic Management Strategy - Afdawaiza, Afdawaiza (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2022)
The COVID-19 pandemic has had a significant effect on various business sectors, including the Business Development Center (BDC) at UIN Sunan Kalijaga, which serves as a business management institution at the university. This study aimed to assess the effect of the COVID-19 pandemic on UIN Sunan Kalijaga's revenue from business sectors managed by the BDC. Additionally, the study aimed to demonstrate how UIN Sunan Kalijaga employed crisis management to respond to the pandemic's effect through various efficiency efforts and optimization of alternative financial aspects. By implementing Business Continuity Management (BCM), Emergency Response Plan (ERP), and Business Contingency Plan (BCP), BDC UIN Sunan Kalijaga Yogyakarta was able to maintain its existence in the first year of the pandemic by posting profits and continued with a positive trend in subsequent years. The findings of this study can be applied practically by providing a business model in times of crisis to ensure the company’s survival. Originality/Value: This study is original in examining the resilience of a university-based business management institution during the COVID-19 crisis, a context rarely explored in crisis management literature. By integrating Business Continuity Management (BCM), Emergency Response Plan (ERP), and Business Contingency Plan (BCP), it demonstrates how UIN Sunan Kalijaga’s Business Development Center sustained profitability and adapted effectively. The findings provide a practical business model for organizations seeking survival strategies in times of crisis, offering both theoretical enrichment and actionable guidance.